Non-specific Effects of Live Attenuated Pertussis Vaccine Against Heterologous Infectious and Inflammatory Diseases - Cauchi, Stéphane; Locht, Camille (Frontiers in Immunology, 2018)
Bordetella pertussis is the agent of pertussis, also referred to as whooping cough, a disease that remains an important public health issue. Vaccine-induced immunity to pertussis wanes over time. In industrialized countries, high vaccine coverage has not prevented infection and transmission of B. pertussis, leading to periodic outbreaks in people of all ages. The consequence is the formation of a large source for transmission to children, who show the highest susceptibility of developing severe whooping cough and mortality. With the aim of providing protection against both disease and infection, a live attenuated pertussis vaccine, in which three toxins have been genetically inactivated or removed, is now in clinical development. This vaccine, named BPZE1, offers strong protection in mice and non-human primates. It has completed a phase I clinical trial in which safety, transient colonization of the human airway and immunogenicity could be demonstrated. In mice, BPZE1 was also found to protect against inflammation resulting from heterologous airway infections, including those caused by other Bordetella species, influenza virus and respiratory syncytial virus. Furthermore, the heterologous protection conferred by BPZE1 was also observed for non-infectious inflammatory diseases, such as allergic asthma, as well as for inflammatory disorders outside of the respiratory tract, such as contact dermatitis. Current studies focus on the mechanisms underlying the anti-inflammatory effects associated with nasal BPZE1 administration. Given the increasing importance of inflammatory disorders, novel preventive and therapeutic approaches are urgently needed. Therefore, live vaccines, such as BPZE1, may offer attractive solutions. It is now essential to understand the cellular and molecular mechanisms of action before translating these biological findings into new healthcare solutions.